Runaway booger - Richtel, Matt 1966- (Harper, 2017)
Find out what happens when Mom leaves Dad in charge with the instructions "No picking of noses" and "No ball in the house."
Keywords: Humorous stories; Stories in rhyme; Mucus / Fiction; Behavior / Fiction; JUVENILE FICTION / Health & Daily Living; JUVENILE FICTION / Humorous Stories; JUVENILE FICTION / Imagination & Play; Picture books for children; Mucus / Easy picture; Humorous fiction; Juvenile fiction / Health & Daily Living; Juvenile fiction / Humorous Stories; Juvenile fiction / Imagination & Play; Conduct of life; Mucus; Fiction; Juvenile works; Picture books; Bilderbuch